2020
DOI: 10.3390/vaccines8040755
|View full text |Cite
|
Sign up to set email alerts
|

Ginseng Stem-Leaf Saponins in Combination with Selenium Promote the Immune Response in Neonatal Mice with Maternal Antibody

Abstract: Neonates acquire from their mothers maternal antibody (MatAb) which results in poor immune response to vaccination. We previously demonstrated that ginseng stem-leaf saponins in combination with selenium (GSe) had adjuvant effect on the immune response to an attenuated pseudorabies virus (aPrV) vaccine. The present study was to evaluate GSe for its effect on the immune response to aPrV vaccine in neonatal mice with MatAb. Results showed that GSe had adjuvant effect on the immune response to aPrV vaccine in neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Indeed, both the NF-κB and MAPK pathways are responsive to ROS activation, resulting in the increased expression of cytokines, chemokines, and other factors involved in the inflammatory response in ruminants [ 43 ]. As a source of antioxidants, dietary supplementation with Se has been shown to enrich innate immune responses and cytokine-production-related terms and pathways, such as the NOD-like receptor signalling pathway, NF-κB signalling pathway, and cytokine-cytokine receptor interaction, via KEGG and GO analysis in mice [ 44 ]. Hence, we found that Se supplementation inhibited the NOD-like receptor signalling pathway, suggesting that exogenous SY may attenuate oxidative stress injury and decrease inflammatory reactions, which may help relieve inflammation and adjust cytokine levels to increase antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, both the NF-κB and MAPK pathways are responsive to ROS activation, resulting in the increased expression of cytokines, chemokines, and other factors involved in the inflammatory response in ruminants [ 43 ]. As a source of antioxidants, dietary supplementation with Se has been shown to enrich innate immune responses and cytokine-production-related terms and pathways, such as the NOD-like receptor signalling pathway, NF-κB signalling pathway, and cytokine-cytokine receptor interaction, via KEGG and GO analysis in mice [ 44 ]. Hence, we found that Se supplementation inhibited the NOD-like receptor signalling pathway, suggesting that exogenous SY may attenuate oxidative stress injury and decrease inflammatory reactions, which may help relieve inflammation and adjust cytokine levels to increase antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-seq-based transcriptomics allows the precise determination of transcript levels and has been used to elucidate the roles of adjuvants in various vaccine immunizations [ 50 , 51 , 52 ]. Moreover, proteomic technology provides information regarding changes in protein expression and posttranslational regulation.…”
Section: Discussionmentioning
confidence: 99%
“…The function of GSe as an adjuvant was also confirmed in neonatal mice carrying the maternal antibodies (MatAbs). Despite the presence of MatAbs, the specific gB antibody and cytokine responses in neonatal mice immunized with aPrV and saline-GSe were markedly increased, and the protection of vaccinated neonates was enhanced [ 153 ]. However, researching natural drugs against PrV is mostly in vitro and the experimental animal stage.…”
Section: Natural Plant Extracts As Potential Anti-prv Drugsmentioning
confidence: 99%